The utilization of village funds during the Covid-19 pandemic and the impact on community welfare in Klungkung Regency - Marhaeni, A A I N; Sudibia, I Ketut; Andika, Gede; Fahlevi, Mochammad (Technium Sustainability, 2023)
The Village Fund Program is a central government program to improve the welfare of rural communities. Each village received a relatively large amount of village funds. However, after their Covid-19, the village funds were diverted to handling the Covid-19 problem. Village funds distributed by the government in general aim to improve the welfare of rural communities due to the unequal welfare conditions between people in rural areas and urban areas. Thus, the village fund program is also expected to eradicate the poor in rural areas. Besides, it is following sustainable development goals (Sustainable Development Goals). /SDGs). The objectives of this research are 1) To analyze the significance of differences in the use of village funds before and after the outbreak of the Covid-19 pandemic in Klungkung Regency; 2) to analyze the effect of using village funds in 2020 after the Covid-19 pandemic on the welfare level of villagers in Klungkung Regency. This research was conducted in Klungkung Regency, especially Klungkung mainland, with the classification of respondents of 3 village officials, 3 village community members, and 1 village community leader. Hence, the respondents in each village are 7 people. The number of villages on Klungkung mainland is 37 villages. Thus, the total number of respondents was 259 people throughout Klungkung Regency. The number of respondents was determined by quota sampling. The sampling technique used was accidental sampling combined with snowball sampling, which was included in the non-probability sampling. For respondents, the village apparatus used probability sampling in each village. In addition, purposive sampling was used for the required informants. Data collection methods were observation, interviews, and in-depth interviews, using descriptive statistical data analysis techniques, regression analysis, and average difference test. The results of the analysis showed that: 1) There was a significant difference in the use of village funds in 2019 and 2020 during the pandemic. In 2020, the use of village funds prioritized handling the Covid-19 pandemic. While the use of village funds in 2019 was used for village administration, village development, community development, and community empowerment; 2) There was a significant positive effect on the use of village funds in 2020 during the Covid-19 pandemic on the welfare level of the population in Klungkung Regency.